A Precise Analysis of the Behavior of Pit Side Tunnels Caused by Deep Excavation - Huasheng Sun; Yuexin Zhao; Yadong Chen; Jiahui Li (Geofluids)
As urbanization gathers pace, projects involving adjacent subway tunnels are increasing, thereby amplifying the need for robust tunnel protection measures. Currently, there exists a notable lack of precise analyses on the three-dimensional (3D) deformation laws and mechanisms of tunnels affected by adjacent deep excavation. Moreover, the influence patterns of retaining wall stiffness and deep excavation depth on the 3D deformation of pit-side tunnels remain unclear. The purpose of this research is to bridge the existing disparity by adopting the hypoplastic model, which effectively captures soil stiffness that is dependent on soil state, strain, and stress path, even at small strains, as well as soil strength, based on reported centrifuge model tests. This approach facilitates a comprehensive, precise numerical analysis of the interaction between deep excavation and preexisting tunnels located outside the retaining wall. The analysis sheds light on the deformation mechanisms and trends of pit-side tunnels not solely confined to the longitudinal axis but extending to the transverse plane as well, while systematically examining the influence of varying excavation depths and retaining wall stiffness on key tunnel parameters, including longitudinal deformation, diameter changes, bending strains, and soil pressure distributions around the tunnels. The study reveals that if the tunnel situated outside the retaining structure lies beneath the foundation pit’s base, deep excavation only slightly deforms the tunnel. However, when the tunnel outside the retaining structure is positioned above the pit’s base, its deformation progressively intensifies with deeper excavation, but the growth rate has a decreasing trend. An enhancement in the stiffness of the retaining wall results in a notable decrease in the deformation exhibited by the adjacent tunnels. The findings contribute to a deeper understanding of the complex responses of pit-side tunnels to excavation activities, ultimately facilitating the design and construction of safer and more resilient urban subway infrastructure.